Carta de José C. Aponte a Emilio S. Belaval - Aponte, José C. (My University, 1968)
José C. Aponte le desea toda clase de éxitos a Emilio S. Belaval.
Keywords: Aponte. José C.--Correspondence.; Aponte. José C.--Correspondencia.; Belaval Maldonado, Emilio S.--Correspondence.; Belaval Maldonado, Emilio S.--Correspondencia.